Pengaruh Kepemimpinan, Iklim Organisasi dan Komitmen Organisasi terhadap Kepuasan Kerja Pegawai pada Kantor Camat Baiturrahman Kota Banda Aceh - Samudra, Putra; M. Yamin; Yuslaidar Yusuf (Jurnal Sains dan Ilmu Terapan, 2026)
This study aims to analyze in depth the influence of leadership, organizational climate, and organizational commitment on employee job satisfaction at the Baiturrahman Subdistrict Office, Banda Aceh City. The research method used is quantitative with a survey approach, designed to obtain an empirical overview of the relationships among variables. This study involved 33 employees as respondents who were selected using a saturated sampling technique, and utilized a structured questionnaire as the primary instrument for data collection. Data analysis was conducted using multiple linear regression, t-tests to examine the partial effects of each independent variable, and F-tests to assess the simultaneous effects overall. The results show that the three independent variables leadership, organizational climate, and organizational commitment have a significant influence on employee job satisfaction, both simultaneously and partially. Among these variables, effective leadership and a conducive organizational climate are the dominant factors in improving job satisfaction.